The impacts of entrepreneurial orientation on the profitability growth of construction firms in Tanzania - Fred Phanuel Okangi; Rizwan Qaisar Danish (Journal of Global Entrepreneurship Research, 2019)
Literature considers entrepreneurship as an important catalyst in the process of improving firm performance and growth. This study analyzes the impacts of entrepreneurial orientation (EO) dimensions (i.e., innovativeness, proactiveness, and risk taking) on the profitability growth of local Tanzania's construction firms. A survey to 132 Tanzanian construction firms was undertaken using a questionnaire. With the help of STATA 13.0 Software, data collected was analyzed by using a multiple regression analysis. The findings show that both innovativeness and risk taking dimensions have a significantly positive effect on the growth of profitability for local Tanzania's construction firms, whereas the proactiveness dimension has a negative significant effect. This study contributes to the field of entrepreneurship in developing countries and enhances the knowledge of the impacts of EO dimensions on the profitability growth of firms (in particular construction firms).
Keywords: 650; Entrepreneurship; Entrepreneurial orientation; Construction industry; Tanzania; Developing countries; innovativeness; Risk taking; Proactiveness